The effect of Verbena officinalis on stress oxidative factors and expression gen of NMDA receptor subunit GluN2B in male rat induced with scopolamine - chakkoshi, Hanieh; Hooshmandi, Zahra; Mahmoodi, Gelavij (Researcher Bulletin of Medical Sciences, 2022)
In traditional medicine, the Verbena officinalis is used to treat depression, seizure, jaundice, fever, anxiety, insomnia, abdominal problems, throat inflammation and thyroid problems. The aim of this study was to evaluate the effect of Verbena officinalis extract on scopolamine-induced memory impairment in rats. In this experimental study, 35 rats were randomly assigned into 5 groups: control group, scopolamine (0.7 mg/kg, i.p., injection) and scopolamine and Verbena officinalis recipients at concentrations of 100, 200 and 400 mg/kg. After 3 weeks of treatment, behavioral tests including passive avoidance memory were performed. The level of malondialdehyde and the antioxidant potential of the serum and brain of the rats were also determined. NMDA receptor subunit GluN2B gene expression was also measured. Treatment of rats with Verbena officinalis increased the secondary delay in the shuttle box test. Treatment with Verbena officinalis also reduced levels of serum and brain tissue malondialdehyde and also increased serum and brain antioxidant capacity. Treatment with 100 doses of Verbena officinalis extract increased the expression level of GluN2B gene in the brain. The findings of this study indicate that the extract of this plant can be a neuropharmacologic agent against memory disorders and oxidative stress induced by scopolamine in rats.